Oral English performance in Danish primary school children: An interactional usage-based approach - Eskildsen, Søren W.; Cadierno, Teresa (Studies in Second Language Learning and Teaching, 2020)
Following the call in Sandlund, Sundqvist, and Nyroos (2016) for incorporating discursive approaches into the field of oral second language (L2) testing, this paper proposes an interactional usage-based approach to the analysis of oral L2 performance. Based on Eskildsen (2018a), we combine analytic tools from usage-based linguistics and conversation analysis. We draw on usage-based linguistics to analyze performance in terms of test-takers’ inventories of linguistic constructions and on conversation analysis to understand their interactional competence in terms of the relation between the linguistic constructions and the actions they are used to accomplish. Performance assessment is thus constructional and interactional. Participants in this pilot study were two Danish primary school children who performed two consecutive oral tasks: a semi-guided interview and a picture-elicited narrative task. Data were analyzed by means of cross-child comparisons and cross-task comparisons within each child. Our data confirm the observation from previous research that simple question-answer(-assessment) sequences dominate oral test formats, but also that the format is sometimes abandoned, which allows for the accomplishment of new social actions. Moreover, the picture-description task affords a different speech exchange system with the interviewer participating more as an active listener when the children do not voluntarily carry out the requested task.